FORMATION OF THE CONCEPT OF "CAPITALISM» - E. I. Naumova; E. G. Sokolov (Дискурс)
The article presents a historical and philosophical reconstruction of the development of the concept of "capitalism" in the 19th - early 20th centuries. The text describes the main stages of conceptualization of the notion starting from when it was first mentioned in the political literature of France and Germany and finishing with its introduction in everyday practice as a sustainable term. An emphasis is made on identifying the content aspects of the term in the context of ideological and theoretical preferences of the era. It is also important that in its discursive and semantic characteristics the notion and the concept of "capitalism" follows the Christian cultural paradigm.